Capturing the Voices of Pseudepigraphic Personae: On the Form and Function of Incipits in the Aramaic Dead Sea Scrolls - Perrin, Andrew B. (Dead Sea discoveries, 2013)
It is widely recognized that the authors of the Aramaic Dead Sea Scrolls often shrouded their tales in first person voices and exhibited a perennial interest in the production and transmission of ancestral booklore. The present study explores the literary convention of the incipit in light of these interrelated methods of pseudepigraphy. Throughout the Aramaic Scrolls incipits introduce entire compositions and putative texts within narratives. Comparative philological analysis reveals that these incipits feature strikingly similar literary-linguistic idioms. However, it is equally apparent that that these common elements were uniquely patterned by individual authors. It is suggested that these commonalities should inform how we conceive of the scribal milieu(s) from which the Aramaic Scrolls emerged and our understanding of pseudepigraphy in early Judaism. The article concludes with a fresh proposal for the function of the title “A Copy of the Writing of the Words of Noah” in 1QapGen 5:29.